Utilization of Artocarpus heterophylla Lamk. As UV Protector In mice exposed to UV-B - Ketut Agus Adrianta; I Made Agus Sunadi Putra (Majalah Obat Tradisional, 2018)
In daily life, Artocarpus heterophylla Lamk., the leaves are rarely used even just as animal feed. In the bark of Artocarpus heterophylla Lamk there are new flavonoid compounds namely morusin, artokarpin, artonin E, cycloartobilosantone, and artonol B. This research is an experimental design with randomized posttest only with control group design. A total of 21 mice were divided into 3 groups, each consisting of 7 mice, group 1: negative control given oral placebo and exposed to UV-B rays, group 2:giving Vitamin C cream 4% mg and exposed to UV-B rays, group 3: giving cream of Artocarpus heterophylla Lamk leaf extract 4% and exposed to UV-B rays. The total of UV radiation dose of 600 mJ / cm² for 3 weeks, then performed a biopsy for examination of the amount of dermis collagen. The average number of collagen in the three groups after treatment was given significantly different (p <0.05). Mean and Significant level of collagen density of group 1 : 51,42 ± 5,16; group P2 ± 91,18 ± 1,13; and P3 group: 88,77 ± 1,10. Conclusion : Cream of 4% Artocarpus heterophylla Lamk leaf extract can increase the amount of collagen density in mice exposed to UV-B rays.